In Vivo Chemoprotective Activity of Bovine Dialyzable Leukocyte Extract in Mouse Bone Marrow Cells against Damage Induced by 5-Fluorouracil - Erika Evangelina Coronado-Cerda; Moisés Armides Franco-Molina; Edgar Mendoza-Gamboa; Heriberto Prado-García; Lydia Guadalupe Rivera-Morales; Pablo Zapata-Benavides; María del Carmen Rodríguez-Salazar; Diana Caballero-Hernandez; Reyes Silvestre Tamez-Guerra; Cristina Rodríguez-Padilla (Journal of Immunology Research)
Chemotherapy treatments induce a number of side effects, such as leukopenia neutropenia, peripheral erythropenia, and thrombocytopenia, affecting the quality of life for cancer patients. 5-Fluorouracil (5-FU) is wieldy used as myeloablative model in mice. The bovine dialyzable leukocyte extract (bDLE) or IMMUNEPOTENT CRP® (ICRP) is an immunomodulatory compound that has antioxidants and anti-inflammatory effects. In order to investigate the chemoprotection effect of ICRP on bone marrow cells in 5-FU treated mice, total bone marrow (BM) cell count, bone marrow colony forming units-granulocyte/macrophage (CFU-GM), cell cycle, immunophenotypification, ROS/superoxide and Nrf2 by flow cytometry, and histological and hematological analyses were performed. Our results demonstrated that ICRP increased BM cell count and CFU-GM number, arrested BM cells in G0/G1 phase, increased the percentage of leukocyte, granulocytic, and erythroid populations, reduced ROS/superoxide formation and Nrf2 activation, and also improved hematological levels and weight gain in 5-FU treated mice. These results suggest that ICRP has a chemoprotective effect against 5-FU in BM cells that can be used in cancer patients.